(untitled) (Archaeologia Adriatica, 2013)
Besides large architectural complexes (the camp principium/municipium forum, the amphitheatre and the exercise campus), archaeological excavations, both earlier ones and those conducted after 2003 by the Town Museum in Drniš and the Department of Archaeology of the University of Zadar, that have taken place in the area of the Roman military camp/municipium of Burnum (Ivoševci near Kistanje) have revealed an extraordinarily large quantity of small archaeological artefacts. Among those from the early stages of life at Burnum in the first half of the first century, there is a series of approximately eighty stamps on fine tableware, which confirms the existence of imports from the Italic area. An analysis of these, together with observations on the overall holdings of the pottery finds, enables detailed insights regarding spatial and chronological supply sources, while a comparison with similar finds from civilian and military sites throws light on the position of Roman Dalmatia on regional trade routes.